Hypomagnesaemia in paediatric population in an intensive care unit. - Deshmukh C (Journal of Postgraduate Medicine, 2000)
AIMS: To determine incidence and risk factors for hypomagnesaemia in children admitted in Paediatric Intensive Care Unit, (PICU). SUBJECTS AND METHODS: Prospective study was carried out on 80 children admitted in PICU. The patients were clinically assessed for nutritional status, neurological status on Glasgow coma scale, congestive cardiac failure, etc. and relevant biochemical parameters including serum and red cell magnesium levels were done. 25 patients of the same age group admitted in general ward who were not in critical state were included as a control group. RESULTS: 70% of PICU patients had hypomagnesaemia, which was more common in patients on aminoglycosides and diuretics. CONCLUSION: In view of complications of magnesium depletion and benign nature of appropriate magnesium therapy critically ill children should have their magnesium level monitored.